The factors associated with job stress among employees in Majlis Daerah Penampang / Sebilia Poumi - Poumi, Sebilia (2008)
Job stress is known as the harmful physical and emotional responses that occur when the requirements of the job do not match the capabilities, resources, or needs of the worker and lead to poor health and even injury. This can be a serious problem when the employees have high level of job stress which might affect their job performance and also their own physical and emotion. Therefore, the purpose of this study is to identify the factors associated with job stress among employees in Majlis Daerah Penampang besides to determine the level of job stress among female and male employees working in this organization. First and foremost, this study is undertaken through the conduct of questionnaire survey on the employees in Majlis Daerah Penampang. The questionnaire was distributed in Majlis Daerah Penampang in four days time. As an overall, the sample was consisted of 100 employees in Majlis Daerah Penampang. The finding of the study shows that most of the respondents have low level of job stress working in this organization. Analysis using the spearman rho correlation revealed that both organizational environment and compensation management have significant correlation with the level of job stress. Thus, these two variables can be a factor associated with job stress among employees in Majlis Daerah Penampang. Herewith, the recommendation has been made in order to improve the organizational environment and compensation management in this organization.